Alienation and anxiety in tourism motivation - Vidon, Elizabeth S.; Rickly, Jillian M. (Elsevier, 2018)
Although underexplored in tourism studies, recent work suggests theories of alienation, as the dialectic of authenticity, have much to contribute to our understanding of tourism motivation. This paper uses three major theoretical tropes (Marxism, existentialism, and Lacanian psychoanalysis) to examine the role of alienation in the motivations of hiking and rock climbing tourists. In particular, these tourists describe only temporary and retrospective relief from anxiety, articulating authenticity as an elusive experience that lies at the horizon, in the next adventure, or in the past as a memory. Alienation is an ever-present component of the human condition, and as such, anxiety is omnipresent in our lives, contributing significantly to touristic desires for escape, rejuvenation, and existential experiences.